Radiative power and x-ray spectrum numerical estimations for wire array Z-pinches. (November 2015) - Olkhovskaya, O G; Basko, M M; Sasorov, P V; Vitchev, I Yu; Novikov, V G; Boldarev, A S; Gasilov, V A; Tkachenko, S I
Abstract: Magnetically driven plasma implosion is studied numerically with the use of a 3D radiative MHD model. We consider a Z-pinch formed by an array of thin tungsten wires. In our calculations we take into account a time-extended plasma production due to a material evaporation by an individual wire caused by the heating electric current. Using a detailed model of the pinch kernel, a soft x-ray radiation intensity is analyzed numerically with resolution of temporal, spatial, angular and spectral radiation characteristics. The results are represented for the conditions pertinent to experiments with cylindrical tungsten wire arrays at Angara-5-1 facility (TRINITI, RF).